ED50 and ED95 of hypobaric ropivacaine during unilateral spinal anesthesia in older patients undergoing hip replacement surgery - Lin, Chao; Xian, Wen-Lin; Xu, Jun; Zhao, Ting; Wu, Zhi-Qiang; Wang, Fang-Jun (Frontiers in Medicine, 2025)
ObjectiveThe spinal block was limited to the operative side during unilateral spinal anesthesia, which has less physiological interference and fewer complications for the patient. The optimal dose of ropivacaine for unilateral spinal anesthesia is still unclear. The aim of this trial was to investigate the ED50 and ED95 of hypobaric ropivacaine during unilateral spinal anesthesia in older patients undergoing hip arthroplasty.MethodsAll patients were administered hypobaric ropivacaine at a spinal anesthetic drug concentration of 0.4%. The trial was conducted using the Dixon sequential method with an initial dose of 10 mg of ropivacaine and a dose difference of 0.5 mg between two consecutive patients. If the subject’s post-block non-surgical leg Bromage score is greater than 0, the next subject’s dose of ropivacaine is reduced by 0.5 mg. If the subject’s post-block non-surgical leg Bromage score is equal to 0, the next patient’s dose of ropivacaine is increased by 0.5 mg. The trial was terminated when alternating positive–negative results were obtained for 7 pairs of patients. ED50, ED95, and the corresponding 95% confidence intervals (CI) for unilateral spinal anesthesia with 0.4% hypobaric ropivacaine were calculated using probit regression analysis. Patients with motor block in the non-surgical leg were identified as the positive group, and patients without motor block in the non-surgical leg were identified as the negative group. Anesthesia onset time, sensory block duration, duration of motor block, the highest dermatomes blocked on the surgical side, and postoperative complications were compared between the two groups.ResultsThe ED50 and ED95 of hypobaric ropivacaine during unilateral spinal anesthesia in older patients undergoing hip arthroplasty were 11.13 mg (95% CI: 10.85–11.42 mg) and 10.30 mg (95% CI: 9.04–10.65 mg), respectively. The drug dosage was higher in the positive group than in the negative group. There was no differences in the onset of anesthesia, block plane of the affected side, the sensory and motor block time of affected side, and the incidences of low blood pressure, nausea and vomiting, chills, urinary retention between groups (p > 0.05).ConclusionThe ED50 and ED95 of hypobaric ropivacaine during unilateral spinal anesthesia in older patients undergoing hip arthroplasty were 11.13 mg (95% CI: 10.85–11.42 mg) and 10.30 mg (95% CI: 9.04–10.65 mg), respectively. Unilateral spinal anesthesia limits the level of block to the operative side with less physiologically disruptive to the patient, more stable perioperative hemodynamics and fewer complications.